18 f-fluorination using tri-tert-butanol ammonium iodide as phase-transfer catalyst: An alternative minimalist approach - Shinde, Sandip S.; Bolik, Kim-Viktoria; Maschauer, Simone; Prante, Olaf (Pharmaceuticals, 2021)
The18F syntheses of tracers for positron emission tomography (PET) typically require several steps, including extraction of [18F]fluoride from H2[18O]O, elution, and drying, prior to nucleo-philic substitution reaction, being a laborious and time-consuming process. The elution of [18F]fluo-ride is commonly achieved by phase transfer catalysts (PTC) in aqueous solution, which makes aze-otropic drying indispensable. The ideal PTC is characterized by a slightly basic nature, its capacity to elute [18F]fluoride with anhydrous solvents, and its efficient complex formation with [18F]fluoride during subsequent labeling. Herein, we developed tri-(tert-butanol)-methylammonium iodide (TBMA-I), a quaternary ammonium salt serving as the PTC for18F-fluorination reactions. The favorable elution efficiency of [18F]fluoride using TBMA-I was demonstrated with aprotic and protic sol-vents, maintaining high18F-recoveries of 96–99%.18F-labeling reactions using TBMA-I as PTC were studied with aliphatic 1,3-ditosylpropane and aryl pinacol boronate esters as precursors, providing 18 F-labeled products in moderate-to-high radiochemical yields. TBMA-I revealed adequate properties for application to18F-fluorination reactions and could be used for elution of [18F]fluoride with MeOH, omitting an additional base and azeotropic drying prior to18F-labeling. We speculate that the tert-alcohol functionality of TBMA-I promotes intermolecular hydrogen bonding, which en-hances the elution efficiency and stability of [18F]fluoride during nucleophilic18F-fluorination.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Copper; Fluorination; Fluorine-18; Nucleo-philic substitution; Phase transfer catalyst; Radiopharmaceuticals